2014
DOI: 10.1093/jat/bku099
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Extensively Washed Hair from Cocaine Users and Drug Chemists to Establish New Reporting Criteria

Abstract: Samples from a self-proclaimed cocaine (COC) user, from 19 drug users (postmortem) and from 27 drug chemists were extensively washed and analyzed for COC, benzoylecgonine, norcocaine (NC), cocaethylene (CE) and aryl hydroxycocaines by liquid chromatography-tandem mass spectrometry. Published wash criteria and cutoffs were applied to the results. Additionally, the data were used to formulate new reporting criteria and interpretation guidelines for forensic casework. Applying the wash and reporting criteria, hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Proposals for discriminating between contamination and incorporated drugs have been proposed [72,73] and may provide sufficient confidence in the future to be accepted as a standardized approach but until such time, the potential role of external contamination must always be considered when interpreting positive hair tests.…”
Section: Incorporation From External Contaminationmentioning
confidence: 99%
“…Proposals for discriminating between contamination and incorporated drugs have been proposed [72,73] and may provide sufficient confidence in the future to be accepted as a standardized approach but until such time, the potential role of external contamination must always be considered when interpreting positive hair tests.…”
Section: Incorporation From External Contaminationmentioning
confidence: 99%
“…First studies in hair were performed looking for o ‐, p ‐ and m ‐OH‐COC . The aim of the present study was the search for hydroxy cocainics in authentic hair samples as specific markers of COC use thus enabling improvement of the criteria regarding a more valid interpretation of COC findings in hair.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively small amounts of drug used to contaminate these hair specimens produced contaminated hair that greatly exceeded the cut-off level to be considered positive. Forensic drug chemists, working under controlled laboratory safety conditions, have shown drug contamination in hair [25]. The hands of a cocaine or methamphetamine smoker or nasal insufflator could be less pristine.…”
Section: Cocaine Methamphetaminementioning
confidence: 99%
“…External contamination considerations have prompted the FBI to stop testing hair for drugs [21]. Some hair testing laboratories have consistently maintained they can distinguish contamination from use [22,23] while others have found that contamination cannot be completely removed, relying on drug metabolites and/or decomposition products to determine drug use [24,25].…”
Section: Introductionmentioning
confidence: 99%